Project management : a systems approach to planning, scheduling, and controlling - Kerzner, Harold (Wiley, 2017)
"The "bible" of project management, updated to address emerging issues Project Management is the bestselling text for students and professionals, presenting a streamlined approach to project management functions in full alignment with PMI®'s latest Project Management Body of Knowledge (PMBOK®). This new 12th edition has been updated to reflect the latest changes found in the PMBOK® Guide—Sixth Edition, and features new coverage of emerging topics including global stakeholder management, causes of failure, agile project management, project governance failure, customer approval milestones, classifying project metrics, and more. Supplementary materials are available for students, working professionals, and instructors. Widely considered the "bible" of project management, this book provides complete, practical guidance on all aspects of project management.  This book provides detailed explanation of the tools and methods used during all stages of a project, reflecting the concepts and standards outlined in the PMBOK® Guide. Understand organizational structures and project management functions Learn how to control costs, manage risk, and analyze trade-offs Examine different methods used for planning, scheduling, QA, and more Work effectively with customers and stakeholders from around the globe As projects increase in scope and complexity, managing scheduling, cost, and specifications across time zones, language barriers, technological differences, and other obstacles requires a systematic approach that accounts for every detail. Project Management is the comprehensive reference to keep within arm's reach throughout all stages of the project. (PMI and PMBOK are registered mark of the Project Management Institute, Inc.)"--